Cardiac and respiratory dysfunction in Duchenne muscular dystrophy and the role of second messengers - Mosqueira, Matias; Zeiger, Ulrike; Förderer, Moritz; Brinkmeier, Heinrich; Fink, Rainer (Medicinal research reviews, 2013)
Duchenne muscular dystrophy (DMD) affects young boys and is characterized by the absence of dystrophin, a large cytoskeletal protein present in skeletal and cardiac muscle cells and neurons. The heart and diaphragm become necrotic in DMD patients and animal models of DMD, resulting in cardiorespiratory failure as the leading cause of death. The major consequences of the absence of dystrophin are high levels of intracellular Ca2+ and the unbalanced production of NO that can finally trigger protein degradation and cell death. Cytoplasmic increase in Ca2+ concentration directly and indirectly triggers different processes such as necrosis, fibrosis, and activation of macrophages. The absence of the neuronal isoform of nitric oxide synthase (nNOS) and the overproduction of NO by the inducible isoform (iNOS) further increase the intracellular Ca2+ via a hypernitrosylation of the ryanodine receptor. NO overproduction, which further induces the expression of iNOS but decreases the expression of the endothelial isoform (eNOS), deregulates the muscle tissue blood flow creating an ischemic situation. The high levels of Ca2+ in dystrophic muscles and the ischemic state of the muscle tissue would culminate in a positive feedback loop. While efforts continue toward optimizing cardiac and respiratory care of DMD patients, both Ca2+ and NO in cardiac and respiratory muscle pathways have been shown to be important to the etiology of the disease. Understanding the mechanisms behind the fine regulation of Ca2+-NO may be important for a noninterventional and noninvasive supportive approach to treat DMD patients, improving the quality of life and natural history of DMD patients.
Gesehen am 09.06.2021